New Aspects in Cesarean Sections - Tsikouras, Panagiotis; Friedrich Von Tempelhoff, Georg; Rath, Werner; Nikos, Nikolettos (IntechOpen, 2023)
This book provides a comprehensive overview of cesarean sections. It provides the most up-to-date evidence to guide obstetric practice and management. The chapter topics include general management of labor, fetal heart rate monitoring, and more specific issues such as multiple pregnancies or pregnancies associated with pregnancy pathology.